Coping with Everyday Stress, Assessment and Relationships, Psychological Adjustment, Well-Being and Socioemotional Adjustment - Francisco Manuel Morales Rodríguez (MDPI AG, 2022)
The use of effective or functional coping strategies guarantees quality of life and psychological well-being in different stages of development [...]